Behavior of coke in the blast furnace for smelting Bayan Obo Mine. (1st February 2022) - Fan, Yingjie; Chai, Yifan; Wu, Jiayi; Zhang, Yunhao; Wang, Yici; An, Shengli; Luo, Guoping
Graphical abstract: Highlights: The behavior of coke in the blast furnace for smelting Bayan Obo Mine was studied. The deteriorating effect of alkali metals on coke was analyzed. The catalytic effect of minerals on coke was analyzed. The gasification reaction of coke was analyzed from the perspective of kinetics. The differences between the feed coke and the tuyere coke were compared. Abstract: A deep understanding of behavior about coke in the blast furnace for smelting Bayan Obo Mine is significantly important to guide its efficient smelting. The feed coke and tuyere coke were taken from 4 # blast furnace in Baotou Steel as the research object. The differences in ash content, microscopic crystal structure, functional group, microscopic pore structure and alkali metal content were compared and analyzed. Then the behavior of coke in the blast furnace for smelting Bayan Obo Mine was obtained. The results show that the coke in the blast furnace undergoes a gasification reaction during the descending process, the chemical bonds are broken, the reactivity is improved, and the strength after the reaction is reduced. There are honeycomb-like pores on the surface of the tuyere coke, and the distribution of pore is uneven. In particular, the coke matrix eroded by slag and iron has rough pore walls, and the pores appear to merge. Alkali metals are enriched in the tuyere coke, the content of alkaline oxides is increased, the temperature of the violent reaction is decreased, and the activation energy of the reaction is decreased. The half-width of the (0 0 2) diffraction peak corresponding to the tuyere coke graphite carbon is sharply reduced, the flat peak disappears, and the peak shape is sharp. The grain size increases, the crystal structure tends to be ordered, and the degree of graphitization increases.